Strategi Pembelajaran PAI Berbasis Quipper School di Sekolah - Pitriyani Mobiliu; Burhanuddin Abdul Karim Mantau; Yanti K. Manoppo (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2025)
This study aims to analyze Islamic Religious Education (IRE) learning strategies based on Quipper School in supporting the learning process in the digital era. The research employed a qualitative approach with data collection techniques including observation, interviews, and documentation. The results indicate that the use of Quipper School supports the implementation of various learning strategies such as flipped classroom, blended learning, project-based learning, collaborative learning, active learning, and assessment and feedback online. The platform enables teachers to deliver learning materials in a more interactive way through videos, practice questions, and discussion forums that can be accessed flexibly by students. In addition, Quipper School assists teachers in managing virtual classrooms and monitoring students’ learning progress online. However, the use of this platform still has several limitations, particularly in assessing affective and psychomotor aspects and its dependence on internet connectivity. Therefore, integrating digital learning with face-to-face learning is important to improve the effectiveness of Islamic Religious Education learning